Social support interventions in health cadres on knowledge and self-efficacy in managing pregnant women with iron deficiency anemia in Indonesia - Neneng Kurwiyah; Syamsul Anwar; Syamikar Baridwan Syamsir; Tantri Puspita; Heru Supriyatno (Malahayati International Journal of Nursing and Health Science, 2024)
Background: Anemia in pregnant women is not only a health concern for the mothers themselves but also has an impact on the health of the fetus. The role of health cadres is crucial in addressing anemia in pregnant women.Purpose: To evaluate the influence of community support interventions on the knowledge and self-efficacy of health cadres in managing anemia in pregnant women in the Thousand Islands region, Indonesia.Method: The research design is quasi-experimental with a single intervention group. A total of 30 health cadres on Kelapa Island and Harapan Island received community support interventions for managing anemia in pregnant women. Assessments of knowledge and self-efficacy were conducted before and after the intervention. Data analysis was performed using paired sample t-tests.Results: Indicate that community support interventions significantly improved the knowledge of health cadres about anemia in pregnant women (p < 0.05). Furthermore, the self-efficacy of health cadres also experienced a significant increase after the intervention (p < 0.05).Conclusion: Community support interventions effectively enhance health cadres' knowledge and self-efficacy in managing anemia in pregnant women in the Thousand Islands region. This study has implications for improving the quality of health services and the management of anemia in pregnant women.